Real-world predictors of survival in patients with limited-stage small-cell lung cancer in Manitoba, Canada - Dawe, David E.; Rittberg, Rebekah; Syed, Iqra; Shanahan, Mary Kate; Moldaver, Daniel; Bucher, Oliver; Galloway, Katie; Reynolds, Kayla; Paul, James T.; Harlos, Craig; Kim, Julian O.; Banerji, Shantanu (Frontiers in Oncology, 2023)
Background Although therapy for limited-stage small-cell lung cancer (LS-SCLC) is administered with curative intent, most patients relapse and eventually die of recurrent disease. Chemotherapy (CT) with concurrent radiotherapy (RT) remains the standard of care for LS-SCLC; however, this could evolve in the near future. Therefore, understanding the current prognostic factors associated with survival is essential. Objective This real-world analysis examines factors associated with long-term survival in patients with LS-SCLC treated with CT in Manitoba, Canada. Methods A retrospective cohort study was conducted using Manitoba Cancer Registry and CancerCare Manitoba records. Eligible patients were aged >18 years and had cytologically confirmed LS-SCLC diagnosed between January 1, 2004, and December 31, 2018, for which they received CT ± RT. Baseline patient, disease, and treatment characteristics and survival duration, characterized as short (<6 months), medium (6−24 months), and long term (>24 months), were extracted. Overall survival (OS) was estimated at one, two, and five years and assessed using Kaplan-Meier methods and Cox proportional hazards models. Results Over the 15-year study period, 304 patients met the eligibility criteria. Long-term survivors comprised 39.1% of the cohort; at diagnosis, this subgroup was younger, more likely to have Eastern Cooperative Oncology Group Performance Status (ECOG PS) 0, and have normal lactate dehydrogenase, sodium, and hemoglobin levels. OS estimates for the entire cohort at one, two, and five years were 66%, 38%, and 18%, respectively. In the ECOG PS 0 subgroup, OS estimates at one, two, and five years were 85%, 52%, and 24%, respectively; OS estimates were 60%, 35%, and 17%, respectively, for ECOG PS 1−2 and were 47%, 23%, and 10%, respectively, for ECOG PS 3−4. OS was significantly higher among patients with normal serum sodium and hemoglobin levels than those with abnormal levels. Univariable hazard regression models found that ECOG PS, age at diagnosis, receipt of prophylactic cranial irradiation (PCI), and thoracic RT were associated with survival. On multivariable hazard regression, ECOG PS and receipt of PCI were associated with survival. Conclusion Survival for greater than two years in patients with LS-SCLC treated with CT ± RT was associated with ECOG PS and receipt of PCI.